The influence of leader–signaled knowledge hiding on tourism employees’ work withdrawal behavior: A moderated mediating model - Xu, Anxin; Zeng, Haimei; Zheng, Qiuqin; Su, Xiaofeng (Frontiers in Psychology, 2022)
Even though organizations encourage the dissemination of knowledge and information among organizational members, the phenomenon of knowledge hiding still exists widely in organizations. The consequences of leader-signaled knowledge hiding are more destructive to the workplace than the consequences of employees’ knowledge hiding. It is particularly necessary to explore the influence mechanism of leader-signaled knowledge hiding on employees’ work behavior. Drawing on Conservation of Resources theory, this study establishes a moderated mediation model with emotional exhaustion as a mediating variable and supervisor-subordinate guanxi as a moderating variable. This study focuses on the consequences of leader-signaled knowledge hiding and divides leader-signaled knowledge hiding into self-practiced knowledge hiding and explicit knowledge hiding. Based on the results of 440 questionnaires from tourism employees, it is shown that leader-signaled knowledge hiding has a positive impact on employees’ work withdrawal behavior. Specifically, leader’s self-practiced knowledge hiding has a greater direct impact on employees’ work withdrawal behavior, while leader’s explicit knowledge hiding has a greater direct impact on employees’ emotional exhaustion. Emotional exhaustion plays a key mediating role in the relationship between leader-signaled knowledge hiding (i.e., self-practiced knowledge hiding and explicit knowledge hiding) and employees’ work withdrawal behavior. Supervisor-subordinate guanxi significantly moderates the positive relationship between leader-signaled knowledge hiding (i.e., self-practiced hiding and explicit knowledge hiding) and employees’ emotional exhaustion. This study is an extension of previous research on knowledge hiding. The results provide a reference for leaders to deal with knowledge hiding and improve organizational knowledge management ability.